ANALISIS MISKONSEPSI PESERTA DIDIK PADA MATERI HUKUM NEWTON DI SMA NEGERI 7 PONTIANAK - Chelyka Yerni Manurung; Haratua Tiur Maria Silitonga; Erwina Oktavianti (Universitas Tanjungpura, 2022)
This study aims to determine the profile and causes of students' misconceptions on Newton's Law material at SMA Negeri 7 Pontianak. The research method used is descriptive qualitative. This research was conducted with a research population taken randomly, namely class X IPA 1 and X IPA 3 with a total of 66 students. The instrument used in this study is a three-tier diagnostic test accompanied by CRI with 15 questions and the causes of misconceptions can be identified by interviewing students. From the diagnostic tests that have been carried out, the results show that students in class X IPA 1 and X IPA 3 have misconceptions. Based on the results of data analysis, the highest misconception is found in item number 12 with 42 students and the lowest misconception is in item number 1 with 16 students. Based on the results of interviews, it was found that the causes of students' misconceptions include preconceptions, associative thinking, students' abilities and students' learning methods that are not correct.